On the challenging variability of LS IV-14°116: Pulsational instabilities excited by the ε-mechanism - Miller Bertolami, Marcelo Miguel (2011)
We investigate the pulsation driving mechanism responsible for the long-period photometric variations observed in LS IV-14°116, a subdwarf B star showing a He-enriched atmospheric composition. To this end, we perform detailed nonadiabatic pulsation computations over fully evolutionary post-He-core-flash stellar structure models, appropriate for hot subdwarf stars at evolutionary phases previous to the He-core burning stage. We found that the variability of LS IV-14°116 can be attributed to non-radial g-mode pulsations excited by the ε-mechanism acting in the He-burning shells that appear before the star settles in the He-core burning stage. Even more interestingly, our results show that LS IV-14°116 could be the first known pulsating star in which the ε-mechanism of mode excitation is operating. Last but not the least, we find that the period range of destabilized modes is sensitive to the exact location of the burning shell, something that might help in distinguishing between the different evolutionary scenarios proposed for the formation of this star.